2015
DOI: 10.1111/ajt.13081
|View full text |Cite|
|
Sign up to set email alerts
|

What’s Hot, What’s New at WTC—Clinical Science

Abstract: More than 3000 abstracts of innovative and exciting findings, covering the whole field of organ transplantation, were presented at the World Transplant Congress 2014. Key areas of presentations across all organs and tissues included HLA antibodies, antibodymediated rejection, living donation, immunosuppression, organ perfusion and surgical procedures. In addition, cutting edge science and future perspectives were presented in state-of-the-art lectures. This review will present highlights of this meeting and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This notion is corroborated by Samstein et al 2 who demonstrated a significant difference in MELD at transplant between DDLT and LDLT (mean, 20.3 vs. 15.2) among 1,036 liver transplant recipients. 3 Analysis of U.S. registry data by Hoehn et al 4 demonstrated a median MELD score of 15 among LDLTs compared to 19 among DDLTs. Between 2007 and 2012, only 14 LDLTs were performed among patients with MELD 28–34 and 3 among patients with MELD 35–40.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is corroborated by Samstein et al 2 who demonstrated a significant difference in MELD at transplant between DDLT and LDLT (mean, 20.3 vs. 15.2) among 1,036 liver transplant recipients. 3 Analysis of U.S. registry data by Hoehn et al 4 demonstrated a median MELD score of 15 among LDLTs compared to 19 among DDLTs. Between 2007 and 2012, only 14 LDLTs were performed among patients with MELD 28–34 and 3 among patients with MELD 35–40.…”
Section: Discussionmentioning
confidence: 99%
“…The wider success of robotic kidney procurement and transplantation seems in fact mainly related to the more favorable anatomy of the kidney, compared with the complex vascular reconstruction needed in liver transplantation. (5) Clear benefits of the robotic approach for LDLT are yet to be demonstrated, and given the significant risk of morbidity and mortality associated with this procedure, only experienced surgical centers should perform it. (6) One of the most interesting perspectives is the possibility to integrate the robotic platform with intraoperative imaging guidance and augmented reality.…”
Section: Robotic Liver Donor Rightmentioning
confidence: 99%